Effectiveness of Using Lemon Aromatherapy to Reduce the Frequency of Nausea and Vomiting in Pregnant Women in the First Trimester - Fairuza, Filda; Nurlaela, Sandy; Parwansyah, Rosiana (Jurnal Biologi Tropis, 2024)
Nausea and vomiting are a common symptom of early pregnancy for pregnant women. Aromatherapy may be used in the treatment to reduce this. The method for utilizing fragrant healing to decrease sickness and spewing can be by breathing in utilizing a diffuser, candles and tissue. Lemon aromatherapy is frequently used during pregnancy and childbirth and is regarded as safe. At TPMB Titin Prihartini, S.ST., Bd, Pandeglang Regency in 2024, the purpose of this study is to determine whether lemon aromatherapy reduces the frequency of nausea and vomiting in pregnant women who are in the first trimester. A one-group pre-test, one-group post-test design is used in this quasi-experimental design. Total Sampling was used for the sampling, with 30 respondents, and observation sheets were used to collect the data. According to the findings of this study, the majority of pregnant women experienced a frequency of nausea and vomiting prior to the intervention, with 27 respondents (90 percent), and after the intervention, with 26 respondents (86.7%) in the mild category. The Wilcoxon signed-rank test, which has a p-value of 0.000 (0.05), is used in statistical tests. These results demonstrate that lemon aromatherapy reduces the frequency of nausea and vomiting in pregnant women in their first trimester at TPMB Titin Prihartini, S.ST., Bd in 2024. Lemon aromatherapy can help alleviate nausea and vomiting in pregnant women who are in the first trimester of their pregnancy.